Instrumented insole for plantar pressure measurement in sports (2018)
Novel technological aids have been developed to evaluate sport performance. Among these tools there are wearable sensors that monitor physical and physiological variables during the execution of exercises. This paper describes the design and construction of an instrumented insole for acquisition and transmission of plantar pressure. The system was designed to support heavy weights, such as in weightlifting. It uses five high-range force sensors located in relevant anatomical points. It can be worn comfortably by the athlete and plantar pressure can be transmitted wirelessly to be registered and visualized in real-time. © Springer Nature Switzerland AG 2018.